A Historical Excursus on the Understanding of the Concept of Matter - Barzdaitis, Juozas (Problemos, 1969)
The article points out that the problem of the concept of matter was one of the main philosophical items in Lithuania in the 16th-17th centuries, and it became particularly important at the end of the 19th century. At the end of the 19th and the beginning of the 20th century the Lithuanian materialists conceived matter without identifying it with any elements of the surrounding world. This period was of great significance to the history of materialism in Lithuania. The Lithuanian materialists came close to the Leninist definition of matter not being able although to overcome some fallacies characteristic of the French and metaphysical materialism on the whole.